Metabolite Profile and Antioxidant Activity of Some Species of Genus Scutellaria Growing in Bulgaria; Plants; Vol. 10, iss. 1 - Georgieva Yo. Yoana; Katsarova M. Mariana; Stoyanov P. Plamen; Mladenov R. Rumen; Denev P. N. Petko Nedyalkov; Teneva D. Desislava; Plotnikov E. V. Evgeny Vladimirovich; Bozov P. Petko; Dimitrova S. Stela (2021, 2021)
Title screen